Kulturowe konteksty dyskursu urzędowego - Malinowska, Ewa (Stylistyka, 2019)
The aim of this paper is to indicate the most important elements of the communicative and cultural context, which exert influence on the official discourse in Poland. Initially, the Roman culture had strongly influenced the shaping of the Polish official discourse; after this, it was the culture of the countries that partitioned Poland, and nowadays, especially after Poland’s accession to the European Union, it is the AngloSaxon culture. The influences of these cultures may be seen in the genre templates of the official documents, as well as in the broadening of the communicative roles and inthe changes of the relations between the discourse subjects. The adoption of the concept of good governance, i.e., the administration which is friendly to citizens and different entities, is of considerable significance in the adjustment of Polish offices to the EU standards.